The Influence of Bank Soundness Level Indicators and Branch Office on Bank Deposit Growth - ika, Ika Wulandari (Universitas Ibn Khladun Bogor, 2023)
This study aims to determine the effect of bank soundness rating indicator and branch offices on deposit growth. Assessment of bank health is proxied by using the ratio of NPL, LDR, IRR, GCG rating, ROA, NIM and CAR. Meanwhile, branch offices were obtained from the branch offices number of bank samples studied. Growth in deposits is proxied by changing on deposits in the year studied with the previous year. This type of research is quantitative research. The research population is banking companies listed on the Indonesia Stock Exchange with the sample of 33 companies in the 2018-2020 period. The sample companies were taken by purposive sampling method. Testing was carried out with multiple linear regression. Hypothesis testing was carried out using the t test. The results showed that NPL, IRR, GCG ratings, ROA, NIM, CAR and branch offices had no effect on deposit growth. Meanwhile, LDR had a negative effect on deposit growth.